(untitled) (Global Journal of Human-Social Science, 2013)
The poor condition of urban transport system in Nigerian cities has now reached a crisis level Although the situation affects women and men previous empirical and theoretical discussions most of the time assumed the uniformity of women and men s experience Transportation Planning and Engineering have been gender neutral It is against this backdrop that the study examines the differential effects of transportation on the varying psychological wellbeing of male and female in Nigeria using Ilorin as case study The study uses primary data which were obtained through a random systematic sampling of 500 households in Ilorin Nigeria Variables used for the study include conditions of urban transport activities and psychological distress information Data collected were analyzed using descriptive and inferential statistics The results showed unprecedented fear that people have for engaging in transport activities Feeling sad and level of worrisome people subjected to while using transport facilities is also high The study also revealed from the regression analysis that transportation have significant effects on the psychological well-being of male and female These findings shows that urban transport condition constitute major threat to psychological well-being of women and men and the effect is more on the women than of men due to gender differences in the socially prescribed roles The study recommends among others the need to improve safety on the street A design of integrated metropolitan transport master plans with a clear vision of train bus and taxis as well as urban motorcycle and non-motorized transport roles are needed The study concludes by emphasizing the need to improve the current state of transport infrastructure in the study area